Rare loss-of-function mutations of PTGIR are enriched in fibromuscular dysplasia - Georges, Adrien (Cardiovasc Res, 2020)
AIMS: Fibromuscular dysplasia (FMD) and spontaneous coronary artery dissection (SCAD) are related, non-atherosclerotic arterial diseases mainly affecting middle-aged women. Little is known about their physiopathological mechanisms. We aimed to identify rare genetic causes to elucidate molecular mechanisms implicated in FMD and SCAD. METHODS AND RESULTS: We analysed 29 exomes that included familial and sporadic FMD. We identified one rare loss-of-function variant (LoF) (frequency(gnomAD) = 0.000075) shared by two FMD sisters in the prostaglandin I(2) receptor gene (PTGIR), a key player in vascular remodelling. Follow-up was conducted by targeted or Sanger sequencing (1071 FMD and 363 SCAD patients) or lookups in exome (264 FMD) or genome sequences (480 SCAD), all independent and unrelated. It revealed four additional LoF allele carriers, in addition to several rare missense variants, among FMD patients, and two LoF allele carriers among SCAD patients, including one carrying a rare splicing mutation (c.768 + 1C>G). We used burden test to test for enrichment in patients compared to gnomAD controls, which detected a putative enrichment in FMD (P(TRAPD) = 8 × 10(−4)), but not a significant enrichment (P(TRAPD) = 0.12) in SCAD. The biological effects of variants on human prostaclycin receptor (hIP) signalling and protein expression were characterized using transient overexpression in human cells. We confirmed the LoFs (Q163X and P17RfsX6) and one missense (L67P), identified in one FMD and one SCAD patient, to severely impair hIP function in vitro. CONCLUSIONS: Our study shows that rare genetic mutations in PTGIR are enriched among FMD patients and found in SCAD patients, suggesting a role for prostacyclin signalling in non-atherosclerotic stenosis and dissection.